2017
DOI: 10.1016/j.jad.2016.11.031
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal depressive symptoms among pregnant women: Evidence from a Southern Brazilian population-based cohort study

Abstract: BackgroundAntenatal depression (AD) is a major public health issue but evidence regarding its prevalence and associated factors in low and middle-income countries (LMICs) is limited. The aim of the study was to estimate the prevalence and identify risk factors for AD among Brazilian pregnant women.MethodsAll women living in the urban area of the city of Pelotas, Southern Brazil, with confirmed pregnancy and estimated delivery date in the year 2015, were invited to take part. Eligible pregnant women were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
63
1
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 37 publications
12
63
1
7
Order By: Relevance
“…e current study also identified that the odds of antenatal depression was about 4 times higher among pregnant women who had family history of mental illness as compared to women who reported no family history of mental illness. is is in line with studies conducted in Ethiopia on perinatal women [36,37] but contradicting with study finding in Pakistan [38]. e variation might be due to the differences of methodology (inclusion criteria) and analysis method which is only square.…”
Section: Prevalence Of Antenatal Depressionsupporting
confidence: 70%
“…e current study also identified that the odds of antenatal depression was about 4 times higher among pregnant women who had family history of mental illness as compared to women who reported no family history of mental illness. is is in line with studies conducted in Ethiopia on perinatal women [36,37] but contradicting with study finding in Pakistan [38]. e variation might be due to the differences of methodology (inclusion criteria) and analysis method which is only square.…”
Section: Prevalence Of Antenatal Depressionsupporting
confidence: 70%
“…It was demonstrated that younger pregnant women were 36% more likely to suffer depression than older pregnant women in Brazil [22]. In a study conducted in the USA, anxiety levels were found to be higher in younger pregnant women [29].…”
Section: Discussionmentioning
confidence: 98%
“…While the Mann Whitney-U test was used to compare the means in two independent groups, the Kruskal Wallis test was used to compare the means in three and more independent groups. In literature, associated with prenatal distress level [7,8,19,22,25] and in the univariate analysis, variables with p < 0.20 were included in the model Multivariate Linear Regression Analysis was performed. The explanatory value of the models was evaluated with the Adjusted R-square (Adj.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations